Global Impact of Major Satisfaction on Academic Achievement: Dampak Global dari Kepuasan Jurusan terhadap Prestasi Akademik - Suaidah, Emilya; Affandi, Ghozali Rusyid (Universitas Muhammadiyah Sidoarjo, 2024)
This study explores the relationship between academic major satisfaction and academic adjustment among university students, recognizing the significance of adjustment for academic success and retention. With a focus on new students at Universitas Muhammadiyah Sidoarjo, the research employs a quantitative correlational approach, utilizing scales to measure both major satisfaction and academic adjustment. Findings reveal a positive correlation (r = 0.531, p < 0.05) between major satisfaction and adjustment, suggesting higher satisfaction enhances adjustment. While major satisfaction contributes 25.1% to adjustment variance, other factors may influence the remaining 74.9%. The study underscores the importance of addressing major satisfaction to improve adjustment and suggests avenues for future research to expand on related variables like mental health and peer support. Highlight: Positive correlation: Major satisfaction boosts academic adjustment in university students. Sampling method: Non-probability sampling used for 370 active students. Limitation: Single variable approach, missing diverse educational levels. Keywoard: Academic Adjustment, Academic Major Satisfaction, University Students, Correlational Study, Retention